TCR-mediated up-regulation of c-FLIPshort correlates with resistance toward CD95-mediated apoptosis by blocking death-inducing signaling complex activity - Kirchhoff, Sabine; Krammer, Peter H. (The journal of immunology, 2000)
To investigate apoptosis resistance upon restimulation in human peripheral blood T lymphocytes, we used the following in vitro model. This model represents the main features of T cell reactivity: freshly isolated PHA-activated T cells cultured in IL-2 for a prolonged period of time develop a CD95 (APO-1/Fas) apoptosis-sensitive phenotype. These T cells represent activation-induced cell death-sensitive T cells during the down phase of an immune response. A fraction of apoptosis-sensitive activated T cells becomes apoptosis resistant upon TCR/CD3 restimulation. CD95 apoptosis sensitivity requires formation of a functional receptor associated death-inducing signaling complex (DISC), i.e., a protein complex of CD95 receptors, the adaptor Fas-associated death domain protein (FADD)/MORT1 and caspase-8 (FADD-like IL-1β-converting enzyme (FLICE), MACH, Mch5). We identified activation of procaspase-8 at the DISC as the main target for the protective activity of TCR/CD3 restimulation. We found that procaspase-8 cleavage is reduced in T cells after TCR/CD3 restimulation. In addition, we detected up-regulation of c-FLIPS (the short splice variant of the cellular FLICE inhibitory protein) and strongly enhanced recruitment of c-FLIPS into the DISC. These data suggest that the recruitment of c-FLIPS into the DISC results in reduced DISC and caspase-8 activity.
Gesehen am 26.04.2021
Im Titel ist der Ausdruck "short" tiefgestellt